ClpL is a functionally active tetradecameric AAA+ chaperone, distinct from hexameric/dodecameric ones. Issue 11 (10th September 2020) - Kim, Gyuhee; Lee, Seong‐Gyu; Han, Seungsu; Jung, Jaeeun; Jeong, Hyeong Seop; Hyun, Jae‐kyung; Rhee, Dong‐Kwon; Kim, Ho Min; Lee, Sangho
Abstract: AAA+ (ATPases associated with diverse cellular activities) chaperones are involved in a plethora of cellular activities to ensure protein homeostasis. The function of AAA+ chaperones is mostly modulated by their hexameric/dodecameric quaternary structures. Here we report the structural and biochemical characterizations of a tetradecameric AAA+ chaperone, ClpL from Streptococcus pneumoniae . ClpL exists as a tetradecamer in solution in the presence of ATP. The cryo‐EM structure of ClpL at 4.5 Å resolution reveals a striking tetradecameric arrangement. Solution structures of ClpL derived from small‐angle X‐ray scattering data suggest that the tetradecameric ClpL could assume a spiral conformation found in active hexameric/dodecameric AAA+ chaperone structures. Vertical positioning of the middle domain accounts for the head‐to‐head arrangement of two heptameric rings. Biochemical activity assays with site‐directed mutagenesis confirmed the critical roles of residues both in the integrity of the tetradecameric arrangement and activities of ClpL. Non‐conserved Q321 and R670 are crucial in the heptameric ring assembly of ClpL. These results establish that ClpL is a functionally active tetradecamer, clearly distinct from hexameric/dodecameric AAA+ chaperones.